2022
DOI: 10.1021/acsami.2c03137
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Ferroelectricity in Sol–Gel-Derived Polycrystalline BiFeO3 Films within a Wide Thickness Range

Abstract: As a promising lead-free ferroelectric, BiFeO3 has a very large intrinsic polarization of ∼100 μC/cm2, enabling its great potential in electronic applications especially in a film format. In this sense, reliable ferroelectric properties are desired; however, pure-phase BiFeO3 films are notorious for their large leakage current, especially of those processed by using the sol–gel methoda facile and industrially scalable method for film preparation. In this study, a protection layer, which can be easily integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The better performance of pure BFO thin films by the sol–gel method has made significant progress in recent years, with comparable or even superior P r (though with larger E c ) than pure BFO thin films prepared by physical methods at a similar thickness range of ∼300 nm. In particular, our prior film protected by an amorphous surface (as adopted in the present work as shown in Figure 6G) 10,27 is similar to polymeric ferroelectrics with a high breakdown strength 52 . Polarization ( P – E ) hysteresis loops and leakage current plots of the BFO thin films annealed at 550°C without an amorphous layer are shown in Figure S5.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The better performance of pure BFO thin films by the sol–gel method has made significant progress in recent years, with comparable or even superior P r (though with larger E c ) than pure BFO thin films prepared by physical methods at a similar thickness range of ∼300 nm. In particular, our prior film protected by an amorphous surface (as adopted in the present work as shown in Figure 6G) 10,27 is similar to polymeric ferroelectrics with a high breakdown strength 52 . Polarization ( P – E ) hysteresis loops and leakage current plots of the BFO thin films annealed at 550°C without an amorphous layer are shown in Figure S5.…”
Section: Resultsmentioning
confidence: 68%
“…Oxygen continually flowed into the rapid thermal processing furnace during annealing. All samples containing an additional amorphous top layer are only pyrolyzed at 400°C (not crystallized) during the heat treatment of the last layer, without annealing treatment (above 500°C they would crystallize), as we have reported in our previous work 10 …”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…During the deposition, the substrate temperature was kept at 600 °C under an oxygen partial pressure (PO 2 ) of 2–13 Pa. To eliminate the effect of thickness on the phase structure and electrical properties, the thicknesses of the prepared BF–BT films were kept at about 300 nm. It has been reported that when the film thickness exceeds a critical value (usually 100–200 nm), the thickness variation has little effect on the physical properties of the ferroelectric films. Before depositing BF–BT films, SrRuO 3 films were prepared on the (001) oriented SrTiO 3 substrate at 650 °C under PO 2 = 13 Pa as the bottom electrode . The SrRuO 3 film showed an atomically flat surface with a root-mean-square roughness below 0.2 nm, providing an excellent surface for the epitaxial growth of the BF–BT films.…”
Section: Experimental Methodsmentioning
confidence: 99%